Family Structure and Female Labour Supply in Mexico City - Xiaodong Gong; Arthur van Soest (Institute for the Study of Labor (IZA), 2000)
This paper investigates labour supply of married women in Mexico City. A static neoclassical structural mode is used. We assume that each woman chooses her labour supply and corresponding income so that her utility is maximized, conditional upon her husband ?s labour supply and earnings. We use a direct translog specification, and include family composition variables as taste shifters. Also taken into account are fixed costs of working, random preferences, and correlation between error terms in wage equations and random preference terms. The wage equation and the labour supply model are estimated jointly by smooth simulated maximum likelihood. We find income elasticities of labour supply of about -0.17, and wage elasticities of about 0.87. The latter is substantially underestimated if the correlation between wage equation errors and random preference terms is not taken into account. We find evidence that the presence of other adult females reduces the negative impact of young children on the mothers? labour supply.
Keywords: C31; O54; C35; J16; J22; 330; Female labour supply; family structure; discrete regression; Frauenerwerbstätigkeit; Arbeitsangebot; Familie; Schätzung; Mexiko-Stadt